Relationship of Fe Supplement Consumption with Anemia in Students of SMAK Tunas Gloria and SMAS Beringin, Kupang City - Adrianus Wio; Lewi Jutomo; Daniela L. A. Boeky (Universitas Nusa Cendana, 2022)
Teenage girls are at high risk for anemia because their Fe needs increase due to growth and menstruation. Anemia can cause fatigue, reduced learning concentration, low academic achievement, reduced work efficiency, and decreased endurance. One of the government's efforts to prevent anemia is by implementing an Fe supplementation program for teenage girls. The implementation did not go well because there were still many teenage girls who were reluctant to take Fe supplements. The aim of this study is to determine the effect of Fe supplement consumption on the incidence of anemia in female students at SMAK Tunas Gloria and SMAS Beringin Kupang City. This research was conducted in November - December 2020 using an analytical survey method with a cross sectional study. The population in this entire study was found to be 61 (31 students at Tunas Gloria High School and 30 students at Beringin High School). The sample for this study were 61 female students. Data analysis included univariate and bivariate using chi square. The results showed there was a relationship between the consumption of Fe supplements and the incidence of anemia (p-value=0.018) and the value of PR=6,66 this means that students who do not take Fe supplements have a 6,66 times greater risk of developing anemia than students who take Fe supplements. The behavior of consuming Fe tablets which is not good can not meet the needs of Fe in a body that is deficient in Fe so that Hb levels in the blood are not normal and anemia occurs in students. Therefore, it is necessary to increase the awareness of young women about the importance of consuming Fe tablets regularly to prevent anemia.